The evaluation of the influence of the body mass index on body posture parameters and selected parameters of the dynamic feet analysis - Sztandera, Paulina; Szczepanowska-Wołowiec, Beata; Kotela, Ireneusz (Journal of Education, Health and Sport, 2019)
Introduction and purpose. The proper process of body shaping in children is extremally important in preventing present and future pain complaints. According to the source literature, a proper body weight is one of the most important factors in children which have an influence on body shaping . The aim of the study was to evaluate the correlations between the body mass index and body posture parameters as well as selected parameters of the dynamic feet analysis. Material and method. The study involved 106 children aged 10‒15 years old from the Świętokrzyskie Voivodeship. While undergoing the examination, the children were dressed in sportswear and had no shoes. The body height was measured using the SECA 213 stadiometer with an accuracy of 0.01 m, the body weight with the Tanita device with an accuracy of 0.01 kg. The next stage involved the assessment of the body posture using Diers Formetric 4D system. Then the child had to walk several times on FreeMed platform. Results. The dependencies of selected parameters of the dynamic feet analysis from the BMI of the examined children were assessed using Spearmann’s correlation. All examined correlations were statistically significant. The dependencies between body posture parameters assessed using Diers Formetric 4D and the BMI of the examined children were assessed by Spearmann’s correlation. A statistically significant negative correlation were observed only between the pelvic torsion and the body mass index. Conclusions. The majority of parameters of the dynamic feet analysis evaluated in the paper increase with the increase of the body mass index of the examined children. Only the parameter, namely the number of steps per minute decreases when the BMI of the examined children grows. Higher values of the body mass index in children were observed when the pelvic torsion to the left was assessed. The BMI of the examined children did not affect the remaining parameters assessing the body posture.